Stellar Motion around Spiral Arms: Gaia Mock Data. Issue 67 (17th July 2015) - Kawata, D.; Hunt, J.A.S.; Grand, R.J.J.; Siebert, A.; Pasetto, S.; Cropper, M.
Abstract : We compare the stellar motion around a spiral arm created in two different scenarios, transient/co-rotating spiral arms and density-wave-like spiral arms. We generate Gaia mock data from snapshots of the simulations following these two scenarios using our stellar population code, SNAPDRAGONS, which takes into account dust extinction and the expected Gaia errors. We compare the observed rotation velocity around a spiral arm similar in position to the Perseus arm, and find that there is a clear difference in the velocity features around the spiral arm between the co-rotating spiral arm and the density-wave-like spiral arm. Our result demonstrates that the volume and accuracy of the Gaia data are sufficient to clearly distinguish these two scenarios of the spiral arms.